China doing business in the Middle Kingdom - Strother, Stuart C. (International business collection., 2012)
This book introduces the reader to essential information regarding business in China. Foreign firms typically engage China as a sourcing location or as a market to sell their goods. China is increasingly taking on a more prominent role in global business. After 30 years of economic reforms that have enabled China to become the workshop of the global economy, we are now witnessing the transformation of the "Middle Kingdom" into one of the world's largest consumer markets and one of the world's most productive centers of innovation. This book covers topics such as history, culture, economy, marketing, sourcing, staffing, etiquette, negotiation, and daily life. Anyone hoping to achieve global business success in the 21st century must be familiar with these concepts.